Opportunities and challenges in promoting youth entrepreneurship in Montenegro - Vesna Karadzic; Radivoje Drobnjak; Manijeh Reyhani (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The purpose of this paper is to examine the opportunities and challenges that youth entrepreneurs are facing in Montenegro, considering all aspects of youth participation in the development of the country. A quality research of several successful young entrepreneurs is presented. Design/methodology/approach - Several successful young entrepreneurs were interviewed. The principles of case study design and method were followed. Data collection involved both macro and micro level analysis of interviews and direct observation. Findings - The analysis shows that although in the areas of youth participation, significant progress has been made in the last several years, youth entrepreneurship programme in Montenegro is still in its early stages of development and needs strong sustainable commitment, assuring the development and efficient functioning of various youth participation mechanisms at the local, regional and national level. It is also essential to continue to standardize and support youth work, youth information and non-formal business education of young people. Surveys show that young people in Montenegro believe they have much to offer and can significantly contribute to all areas of the society's development. However, their potential remains greatly untapped due to certain obstacles that they face. There are needs for encouraging programs to inform youth about the value of their participation in all aspects of society. Research limitations/implications - The main limitations were access to a greater number of successful young entrepreneurs making the analysis more descriptive and conclusive. Originality/value - The paper supports understanding of the complex employment challenges and opportunities facing youth and stimulates discussion on how to address this key development issue.
Keywords: M13; M31; O40; 330; Entrepreneurship; Youth; Montenegro; Business; Employment